Incidence, Demographics, and Outcomes of Penetrating Trauma in Sweden During the Past Decade - Günther, Mattias; Dahlberg, Martin; Rostami, Amir; Azadali, Ali; Arborelius, Ulf P.; Linder, Fredrik; Rostami, Elham (Frontiers in Neurology, 2021)
Trauma injury is the sixth leading cause of death worldwide and interpersonal violence is one of the major contributors in particular regarding injuries to head and neck. The incidence, demographics, and outcomes of penetrating trauma reaching hospitals in Sweden are not known. We report the largest, nationwide epidemiological study of penetrating injuries in Sweden using the SweTrau (The Swedish Trauma Registry). A multi-center retrospective descriptive study of 4776 patients with penetrating injuries in Sweden, between 2012 and 2018. Due to the increase of coverage of the SweTrau registry during same period we chose to analyze the average number of cases for the time intervals 2013-2015 and 2016-2018 and compare those trends to the reports of the Swedish National Council for Crime Prevention (Brå) as well. A total of 663 patients had ISS ≥ 15 at admission and were included in the study. 368 (55.5%) were stab wounds (SW), 245 (37.0%) gunshot wounds (GSW), and 50 (7.5%) other trauma. A majority of the cases involved injuries to head, neck and face. SW increased from 145 during 2013-2015 to 184 during the second period of 2016-2018. The increase was greater for GSW from 92 up to 141 during same respective periods. This trend of increase over time was also seen in head, neck, and face injuries. The 30-day mortality was unaffected (48% to 47%) in GSW and trended towards lower in SW (24% to 21%) when comparing 2013-2015 with 2016-2018. Patients with head trauma had 45% mortality compared to 18% for non-head trauma patients. Head trauma also resulted in worse outcomes, only 13% had GOS 5 compared to 27% in non-head trauma. The increasing number of cases of both SW and GSW corresponded well with reports from Brå although further studies are needed to also address deaths outside of hospitals and not registered at Swetrau. The majority of cases had injuries to head, neck, and face that were associated with higher mortality and poor outcomes. Further studies are needed to understand the contributing factors to these worse outcomes in Sweden and whether more targeted trauma care of these patients can improve outcomes.